Access and benefit sharing of genetic resources. Making it work for family farmers - Pistorius, R.; Bruil, J.; Vernooy, Ronnie (Centre for Learning on Sustainable Agriculture (ILEIA), 2016)
Access and benefit sharing of plant genetic resources is a crucial but very complex, political and legalistic matter. Does the formal system work for family farmers? It poses many challenges. At the same time, farmers around the world are leading successful initiatives for access and benefit sharing. This issue of Farming Matters presents cases that demonstrate the limited extent to which family farmers have been able to benefit from the ‘formal’ ABS process. It also uncovers some of the effective principles and mechanisms for access and benefit sharing that are part and parcel of farmers’ everyday practices, such as community seed banks, and successful collaborations between researchers and farmers. Some of these arrangements have links with the formal system.